Analysis of the surgical learning curve using the cumulative sum (CUSUM) method12. Issue 7 (28th January 2013) - Maguire, Turlough; Mayne, Christopher J.; Terry, Tim; Tincello, Douglas G.
Abstract Aims The concept of the "learning curve" is a term that has become increasingly prevalent in medical literature. Using a unique Female Urology fellowship program running over the last 3 years, we set out to better define the learning process for mid‐urethral slings. Methods We examined surgical outcomes for six urology trainees who participated in the 6‐month program from 2006 to 2011. We identified all retropubic mid‐urethral sling procedures they had performed. Demographics included age, BMI, and smoking status. Outcomes focused on complication rates, as well as a subjective patient assessment. Analysis was by the cumulative sum method. Results Six trainees performed 187 retropubic slings during their fellowships. Mean age was 54 (SD ± 12.7), mean BMI was 29.5 (SD ± 5.5). One hundred sixty‐five (88%) patients only underwent a mid‐urethral tape with 22 (12%) undergoing a concomitant procedure. There were 5 cases of bladder perforation, 1 case of urethral injury, 25 cases of voiding dysfunction, and 8 cases of mesh exposure. One hundred sixty‐seven out of 180 patients reported a cure or improvement. All complications occurred in the first 4 months of training. CUSUM analysis of voiding dysfunction showed that four out of six trainees did not reach the expected incidence of voiding dysfunction within the completed fellowship. Bladder perforation showed a similar trend. Conclusion CUSUM analysis is an underused tool for the analysis of surgical competence. The learning curve for retropubic sling surgery is variable and may be longer than is often acknowledged. We suggest the focus of surgical training should move away from absolute numbers to look at training in an individualized manner. Neurourol. Urodynam. 32: 964–967, 2013. © 2013 Wiley Periodicals, Inc.